2008
DOI: 10.1161/circulationaha.107.716712
|View full text |Cite
|
Sign up to set email alerts
|

Catheter Ablation for Atrial Fibrillation in Patients With Obesity

Abstract: Background-Obesity is a risk factor for atrial fibrillation and other cardiovascular conditions. Our objective was to determine whether catheter-based ablation effectively treated atrial fibrillation in obese patients. Methods and Results-Five hundred twenty-three consecutive patients with symptomatic, medication-refractory atrial fibrillation underwent catheter ablation. Patients were grouped by body mass index (lean, Ͻ25 kg/m 2 ; overweight, 25 to 29.9 kg/m 2 ; obese, Ն30 kg/m 2 ). Outcome and quality of lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
111
4
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(132 citation statements)
references
References 31 publications
(24 reference statements)
13
111
4
4
Order By: Relevance
“…Although the LA enlargement that is usually present in obese patients seems to work as a facilitating factor in AF recurrence, Cha et al found that AF catheter ablation was similarly effective in obese patients, 4 which was in good accordance with the study of Tang et al 1 In the latter study, AF recurrence mostly occurred early after catheter ablation, and an electrical reconnection between the LA and PV was confirmed in most patients who underwent repeat catheter ablation. Because AF recurrence did not different between the groups with simple PV isolation or PV isolation plus substrate modification, the primary reason for AF recurrence was thought to be electrical reconnection, and the development of triggered firing from a new, non-PV focus, and/or progression of structural and electrical remodeling, seemed to play a less important role.…”
Section: Article P 438 Catheter Ablationsupporting
confidence: 60%
“…Although the LA enlargement that is usually present in obese patients seems to work as a facilitating factor in AF recurrence, Cha et al found that AF catheter ablation was similarly effective in obese patients, 4 which was in good accordance with the study of Tang et al 1 In the latter study, AF recurrence mostly occurred early after catheter ablation, and an electrical reconnection between the LA and PV was confirmed in most patients who underwent repeat catheter ablation. Because AF recurrence did not different between the groups with simple PV isolation or PV isolation plus substrate modification, the primary reason for AF recurrence was thought to be electrical reconnection, and the development of triggered firing from a new, non-PV focus, and/or progression of structural and electrical remodeling, seemed to play a less important role.…”
Section: Article P 438 Catheter Ablationsupporting
confidence: 60%
“…Otyłość może zwiększać częstość nawrotów AF po ablacji przezcewnikowej [298][299][300][301], a ważnym potencjalnym czynnikiem zakłócającym jest obturacyjny bezdech senny. Otyłość powiązano również z większą dawką promieniowania i częstością występowania powikłań podczas ablacji AF [302,303].…”
Section: Ablacja Przezcewnikowa U Otyłych Pacjentówunclassified
“…Otyłość powiązano również z większą dawką promieniowania i częstością występowania powikłań podczas ablacji AF [302,303]. Warto zauważyć, że poprawa objawowa po przezcewnikowej ablacji AF u otyłych pacjentów wydaje się podobna jak u pacjentów o prawidłowej masie ciała [298]. Biorąc pod uwagę potencjał zmniejszenia częstości występo-wania epizodów AF poprzez redukcję masy ciała (patrz rozdz.…”
Section: Ablacja Przezcewnikowa U Otyłych Pacjentówunclassified
“…4 Patients with increased body mass index who required prolonged time for the completion of pulmonary vein isolation (PVI) were at greater risk for the development of complications because of their comorbid conditions. 5 Additionally, mechanical issues leading to high complications, such as difficulty with endotracheal intubation, possible hemodynamic intolerance to general anesthesia, vascular access issues, and substantially higher radiation exposure, remain significant concerns to be addressed.…”
Section: Obesitymentioning
confidence: 99%